Numerical Study of the Thermal Performance of a Food Retort Machine Considering Grid Resolution and Operating Temperature - Ridho Ardiansyah; Hisyam Ma’mun; Muhamad Safi’i (Fakultas Teknik Universitas Samudra, 2026)
Thermal sterilization processes in the food industry require uniform heat distribution so that the microbiological safety of products can be achieved without causing excessive energy consumption. A retort machine is one of the sterilization technologies widely used because it can extend the shelf life of packaged food products. This study aims to numerically evaluate the thermal performance of a retort machine by considering the effects of grid number and operating temperature on temperature distribution, pressure, and heat transfer coefficient. The benefit of this study is to provide a technical basis for selecting the optimum grid and effective operating temperature to support an accurate, stable, and efficient sterilization process. The significance of this study lies in the need of the food industry for a thermal analysis method that can reduce dependence on direct experiments, which require substantial cost, time, and resources. The method used in this study is Computational Fluid Dynamics (CFD) simulation with the realizable k-ε turbulence model, grid variations ranging from 1,145,681 to 4,027,933 elements, a flow velocity of 2 m/s, and inlet temperature variations of 115°C, 117°C, 121°C, and 123°C. The results show that the grid with 3,063,355 elements is the optimum grid because the temperature change compared to the higher grid is not significant. An increase in inlet temperature also increases the surface temperature and heat transfer coefficient. The operating temperature of 121°C showed stable and effective thermal performance based on the CFD simulation results, so it can be considered an initial recommendation in optimizing the thermal performance of the retort. However, its application on an industrial scale still requires further study of the F0 value, sterilization time, product quality, and energy consumption.